The role of collagen in joint disorders: Applications in orthopedics, rheumatology, and sports medicine - Wojcieszek, Maria; Szałajska, Julia; Wierzejska, Natalia; Domański, Mikołaj; Kopczyńska, Barbara; Czyżniewska, Oliwia; Czupryńska, Karolina; Otręba, Karina (Quality in Sport, 2024)
Joint diseases are prevalent in orthopedic, rheumatological, and sports medicine fields, significantly impacting patients’ quality of life. Collagen, a primary component of connective tissues, has emerged as a therapeutic agent for these conditions. This article explores the applications of collagen in joint diseases, comparing oral and intra-articular administration, evaluating optimal dosages, assessing single versus long-term therapies, discussing side effects, and examining the benefits of hydrolyzed versus non-hydrolyzed collagen. Additionally, explore various sources of collagen and their respective advantages for patient care.